Sport Entrepreneurship: Definition and Conceptualization - Paul Jones (Journal of Small Business Strategy, 2022)
The domain of sport entrepreneurship has become firmly established in the scientific community, but there remains an ongoing debate about the true meaning of sport entrepreneurship. Is sport entrepreneurship a distinct characteristic of sport, or is it a deduction of innovative behavior to create business in sport? Current conceptual progress is limited in important aspects of opportunity exploitation and value creation. This study offers a fundamental reconciliation based on a thorough literature review on the distinct nature of sport and theoretical constructs of entrepreneurial research to decode and recompose the concept of sport entrepreneurship. The presented effort towards a universally accepted definition is based on a process perspective and by integrating sport-related social entrepreneurship, this study is a prelude to improve the coherence of the future paradigm of sport entrepreneurship.